Interference of anthocyanin extracted from black soybean coats on aflatoxin B1-human serum albumin in the binding process. Issue 9 (2nd September 2021) - Fan, Tingting; Xie, Yanli; Sun, Shumin
ABSTRACT: The effect of the anthocyanin cyanidin-3-O-glucoside (C3G) and its main gastrointestinal metabolites (PCA and PGA) on the binding of AFB1 and HSA were studied via spectrometry. C3G is relatively stable in the gastric environment, and the intestinal environment promotes its metabolism into PCA and PGA. Binary fluorescence experiments showed that both AFB1 and C3G, including PCA and PGA, can react with HSA. AFB1, C3G and PCA can bind at site I and site II of HSA; PGA binds at site II. The presence of C3G/PCA/PGA inhibits the degree of quenching. C3G/PCA does not change the quenching mechanism; it is still static quenching; however, dynamic quenching occurs in the (AFB1 -HSA)-PGA system. In addition, the apparent binding constant and number of binding sites of AFB1 -HSA also diminish to different degrees. C3G and its metabolites (PCA and PGA) interfere with the interaction between AFB1 and HSA, and can reduce AFB1 transport at pH 7.4 in vitro. Abbreviations: C3G: cyanidin-3-O-glucoside; M: metabolite; PCA: protocatechuic acid; PGA: phloroglucinol aldehyde; AFB1 : aflatoxin B1 ; HSA: human serum albumin.